2017
DOI: 10.1111/lam.12701
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of foodborne pathogenic and spoilage micro-organisms using ultraviolet-A light in combination with ferulic acid

Abstract: Microbial contamination is one of the most serious problems for foods, fruit and sugar thick juices. UV light is suitable for the nonthermal decontamination of food products by inactivating the contaminating micro-organisms. However, UV-A exposure is insufficient for disinfection. This study demonstrates that the combination of UV-A LED light (350-385 nm), which is not hazardous to human eyes and skin, and ferulic acid (FA), a known phytochemical and food additive, provides synergistic antimicrobial activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The photofungicidal effect of the FA and UV-A combination against Saccharomyces sp. was similar to the bactericidal efficacy against E. coli dependent on UV-A light fluence (Shirai et al, 2017). Previous studies examining photobactericidal activity against E. coli and Staphylococcus aureus found that adsorption of phenolic acids onto the cell surface and their subsequent incorporation into the bacterial membrane plays an important role in mediating the bactericidal effect (Nakamura et al, 2015;Shirai & Yasutomo, 2019).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The photofungicidal effect of the FA and UV-A combination against Saccharomyces sp. was similar to the bactericidal efficacy against E. coli dependent on UV-A light fluence (Shirai et al, 2017). Previous studies examining photobactericidal activity against E. coli and Staphylococcus aureus found that adsorption of phenolic acids onto the cell surface and their subsequent incorporation into the bacterial membrane plays an important role in mediating the bactericidal effect (Nakamura et al, 2015;Shirai & Yasutomo, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…was similar to the bactericidal efficacy against E . coli dependent on UV‐A light fluence (Shirai et al, 2017). Previous studies examining photobactericidal activity against E .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations